A Comparison of Conventional and Microwave Decalcification and Processing of Tooth and Mandibular Bone Specimens - A. Thirumal Raj; Shankargouda Patil; Roopa S Rao (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Any laboratory procedure exposes the technician and the pathologists to the hazardous effects of chemicals. Conventional procedures like decalcification and histoprocessing employed in laboratories are labour intense and time consuming thereby delaying the report dispatch. The present study was an attempt to employ a kitchen microwave to hasten the process and facilitate faster and accurate reporting; thus, benefitting the technician, pathologist and the patient. Aim: To compare conventional and microwave based decalcification, processing and staining of tooth and mandibular bone specimens using 5% nitric acid as decalcifying agent. Materials and Methods: The sample included formalin fixed 180 tooth specimens (60 incisors, 60 premolars, 60 molars) and 60 mandibular bone specimens (approx 0.5cm each). The hard tissue specimens were subjected to varying combination of conventional and microwave decalcification, processing and staining. The entire procedure was blinded and evaluated by two examiners. Results: Conventional Decalcification (CD), processing and staining produced the utmost quality, though consuming a relatively longer duration. Microwave reduced the total decalcification time by half and retained the diagnostic quality of the specimens. On the contrary the microwave based processing and staining caused significant damage to the tissues rendering sections un-diagnostic. Conclusion: A combination of Microwave Decalcification (MD) followed by Conventional Processing (CP) and staining would be ideal to hasten the overall laboratory time with minimal compromise on tissue quality.